Christianity and recent speculations: Six lectures by ministers of the Free church - Candlish, Robert Smith; Smith, Thomas; Rainy, Robert; Blaikie, William Garden; Crichton, Andrew; Duns, John (J. Maclaren, 1866)
The Bible not inconsistent with science, by Thomas Smith.--On the place and ends of miracles, by Robert Rainy.--Spiritual Christianity in relation to secular progress, by W.G. Blaikie.--The purpose and form of Holy Scripture, by Andrew Crichton.--Prayer and natural law, by John Duns.--The Sabbath, by R.S. Candlish.